Identifying the roadmap for passenger transportation in Curitiba by means of LCA and mathematical optimization - Cuzinsky, Fernando Cesar (2019)
In order to set the priorities of strategies for climate change mitigation in cities, this work proposes roadmaps for passenger transportation for the city of Curitiba between 2017 and 2035. We suggested an integrated approach that combines backcasting scenarios, Life Cycle Assessment (LCA) and mathematical optimization to prioritize the activities and develop the roadmaps. The quantitative roadmap for passenger transportation was modeled as a mixedinteger linear programming (MILP). Global Warming Potential and Global Temperature Potential impacts were analyzed. From our approach it was found that for both roadmaps, subway does not need to be implemented, and urban buses can supply the transportation demand. Whether an improvement would occur in public transportation, increasing its participation in passenger transportation, the Global Warming Potential for 100 years can be 28% lower in 2035 compared to the baseline scenario. This baseline is also defined by GWP100 impact. This research yields a model to estimate the cities’ impacts and to develop quantitative roadmaps to reduce the climate change for passenger transportation. In addition, the present findings provide two roadmaps for public and individual transportation for Curitiba.